2021
DOI: 10.3390/nu13051706
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Gene Signature of (−)-Oleocanthal Formulation Treatments in Heterogeneous Triple Negative Breast Tumor Models: Oncological Therapeutic Target Insights

Abstract: Triple negative breast cancer (TNBC) heterogeneity and limited therapeutic options confer its phenotypic aggressiveness. The discovery of anti-TNBC natural products with valid molecular target(s) and defined pharmacodynamic profile would facilitate their therapeutic nutraceutical use by TNBC patients. The extra-virgin olive oil (EVOO) is a key Mediterranean diet ingredient. S-(−)-Oleocanthal (OC) leads the bioactive anti-tumor EVOO phenolic ingredients. A previous study reported the solid dispersion formulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 93 publications
(140 reference statements)
1
2
0
Order By: Relevance
“…Importantly, this model showed that the phenotypic effects were oriented toward reduced malignancy independently on sLe x inhibition [67]. Consistent with TCGA data, experimental studies with triple negative breast cancer cell lines have shown a positive correlation between high B4GALNT2 and malignancy [68,69]. In particular, it has been shown that the B4GALNT2 protein is able to interact with proteins of the major histocompatibility complex (HLA-B) [69].…”
Section: How B4galnt2/sd a Play A Role In Cancersupporting
confidence: 74%
“…Importantly, this model showed that the phenotypic effects were oriented toward reduced malignancy independently on sLe x inhibition [67]. Consistent with TCGA data, experimental studies with triple negative breast cancer cell lines have shown a positive correlation between high B4GALNT2 and malignancy [68,69]. In particular, it has been shown that the B4GALNT2 protein is able to interact with proteins of the major histocompatibility complex (HLA-B) [69].…”
Section: How B4galnt2/sd a Play A Role In Cancersupporting
confidence: 74%
“…In vivo, intragastric administration with oleocanthal (7.5 mg/kg daily for seven weeks) suppressed the initiation and incidence of mammary carcinogenesis in MMTV-PyVT mice developing spontaneous mammary tumors and in a breast cancer patient-derived xenograft model, concomitantly with transcriptomic changes in tumors and with the downregulation of Myc being a key event [155]. In an orthotopic nude mouse model using the MDA-MB-231/GFP human breast cancer cell line, 5 mg/kg (-)-oleocanthal reduced tumor growth and inhibited tumor activation of c-Met, the proliferation marker Ki-67 and the expression of vessel formation marker CD31 [156].…”
Section: Oleocanthalmentioning
confidence: 99%
“…Little is known about B4GALNT2 in BRCA. A recent study reported a systemic upregulation of B4GALNT2 in an experimental model of breast cancer [ 45 ]. Consistently, TCGA data analysis showed that in normal breast tissues as well as in the majority of BRCA tissues, the level of B4GALNT2 mRNA expression was nearly undetectable ( Figure 5 C,D), although a minority of the cancer cases displayed a level of activity similar with that of colon.…”
Section: Sd a / B4galnt2 In Development Differentiation And Cancermentioning
confidence: 99%